Riffaterre's Semiotic Study on Elegi by Joko Pinurbo - Sugiyo Sugiyo; Siti Nurmila (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
This study aims to describe the expression of anxiety in Elegi's poetry through heuristic and hermenic reading as well as the unsustainability of expressions in poetry, matrices, variants, and hypograms in Joko Pinurbo's five poems. This descriptive qualitative research was analyzed through Riffaterre's semiotic approach. Research data in the form of stanzas and lines in the poem Elegi by Joko Pinurbo. The source of this research is a collection of poetry books Book of Sleep Exercise X Song Moon Poetry by Jokpin Pinurbo. The results showed that (1) through reading heuristics and hermeneutics showed that there were themes taken by anxiety; (2) The unsustainability of the expression put forward by Riffaterre includes the replacement of meaning, deviation of meaning, and creation of meaning; (3) The matrix in Jokpin's